Analyzing customer sentiments in genshin impact: a business intelligence perspective on player perception - Kurnianingrum, Dian; Wijaya, Andrian; Jumri, Isma Addi; Savitri, Mila Andria; Tanuar, Evawaty; Karmagatri, Mulyani (2023)
Customer perception plays a pivotal role in determining the success of a game in the competitive market landscape. It encompasses how players perceive various aspects of the game, including its mechanics, visuals, story, character design, and overall experiential quality. In data analysis, sentiment analysis has emerged as a powerful tool for gaining valuable insights into customer perception. This research aims to employ sophisticated sentiment analysis techniques to understand customer perception in the context of Genshin Impact comprehensively. Through sentiment analysis, this study explores the intricate relationship between customer perception and player sentiments expressed concerning Genshin Impact. An analysis of categorized tweets reveals significant sentiment patterns associated with using specific words. Negative sentiment is observed in tweets containing words such as 'lazy,' 'retired,' 'uninstalled,' and 'sad,' indicating the presence of unfavorable content. Conversely, positive sentiment is associated with words like 'play,' which holds the highest frequency in positive keywords. Genshin Impact players use this term to express their enjoyment and satisfaction from engaging with the game. Additional positive keywords include 'interesting,' 'funny,' 'gacha' (a term related to acquiring characters in the game), 'lore,' and 'characters.' By leveraging sentiment analysis techniques, this research contributes to a comprehensive understanding of customer perception in Genshin Impact. The findings shed light on the prevailing sentiments of players and provide insights into the factors contributing to positive and negative perceptions of the game.